VD_FINDINFO ML / 2014 / 121 vom 28. Mai 2014 - VD Tribunal cantonal (2014)
OPPOSITIONLP, RÉVOCATIONEN GÉNÉRAL, PRINCIPE DE LA BONNE FOI, AUTORITÉ JUDICIAIRETRIBUNAL, DÉPENS | 106 al. 1 CPC (CH), 52 CPC (CH), 56 CPC (CH), 20 al. 2 TDC, 3 TDC, 6 TDC